Dynamic of the Singularly Perturbed Nicholson Equation - Elabd, Neamaa A.; Al-Fadel, Masouda M. A. (جامعة الزيتونة الدولية, 2022)
In this paper, we consider a class of singularly perturbed equations with a parameter ∈. By letting the perturbation parameter tends to zero, such an equation is formally reduced to a scalar difference equation. Local stability analysis of fixed points is investigated. The method of steps is used to discretize the system. Moreover, Numerical simulations including Lyapunov exponent, bifurcation and chaos is carried out to confirm the theoretical analysis obtained to explore more complex dynamic of the system.
Keywords: المعادلات التفاضلية -- المعادلات المضطربة -- معادلة نيكولسون -- المحاكاة العددية -- الأس ليابونوف -- النقطة الثابتة